Analisis Laju Pertumbuhan Dan Kontribusi Penerimaan Pajak Reklame Terhadap Pendapatan Pajak Daerah (Studi Kasus Pada Kantor Badan Pendapatan Daerah Kabupaten Sikka) - Thalia Aurora Starenya Gewar (Universitas Maritim AMNI Semarang, 2023)
The purpose of this study was to determine and analyze the Growth Rate and Contribution of Advertising Tax Revenue to Sikka District Regional Tax Revenue. The type of research used is descriptive-quantitative. Quantitative-descriptive is a method that aims to create an objective picture or description of a situation using numbers starting from data collection, interpretation of the data as well as the appearance and results. The data analysis technique in this study uses the growth rate analysis formula and the contribution formula. The results of this study show that the average growth rate of advertisement tax revenue for 2017-2021 reaches 72% and the growth rate of local tax revenue reaches 49%. The average contribution of advertisement tax revenue to regional taxes in 2017-2021 reached 1.07% with very low criteria. Efforts made by BAPENDA of Sikka Regency to increase advertisement tax revenue through intensification and extensification.